Three cases of mcr-1-positive colistin-resistant Escherichia coli bloodstream infections in Italy, August 2016 to January 2017 - Corbella, Marta (Euro Surveill, 2017)
We describe three cases of bloodstream infection caused by colistin-resistant Escherichia coli in patients in a tertiary hospital in Italy, between August 2016 and January 2017. Whole genome sequencing detected the mcr-1 gene in three isolated strains belonging to different sequence types (STs). This occurrence of three cases with mcr-1-positive E. coli belonging to different STs in six months suggests a widespread problem in settings where high multidrug resistance is endemic such as in Italy.